2022
DOI: 10.1021/acs.analchem.2c01263
|View full text |Cite
|
Sign up to set email alerts
|

Toward Nanomolar Multi-Component Analysis by 19F NMR

Abstract: The widespread application of nuclear magnetic resonance (NMR) spectroscopy in detection is currently hampered by its inherently low sensitivity and complications resulting from the undesired signal overlap. Here, we report a detection scheme to address these challenges, where analytes are recognized by 19 Flabeled probes to induce characteristic shifts of 19 F resonances that can be used as "chromatographic" signatures to pin down each lowconcentration analyte in complex mixtures. This unique signal transduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…35 The synthetic method gives access to 19 F-labeled probes bearing as many as 72 chemically equivalent 19 F atoms, which allows nanomolar multicomponent analysis of complex mixtures. 36 To achieve a highly sensitive enantioanalysis using NMR, we set out our investigation by the design and synthesis of chiral 19 F-labeled probes bearing massive amounts of 19 F atoms. The palladium pincer complex provides an ideal platform to test the feasibility of our approach to detect trace amounts of chiral analytes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 The synthetic method gives access to 19 F-labeled probes bearing as many as 72 chemically equivalent 19 F atoms, which allows nanomolar multicomponent analysis of complex mixtures. 36 To achieve a highly sensitive enantioanalysis using NMR, we set out our investigation by the design and synthesis of chiral 19 F-labeled probes bearing massive amounts of 19 F atoms. The palladium pincer complex provides an ideal platform to test the feasibility of our approach to detect trace amounts of chiral analytes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This strategy, which produces a chromatogram-like output, is often referred to as recognition-enabled chromatographic (REC) NMR. , Based on the unique chemical reactivity of the hypervalent iodine compound, we develop an efficient method for the introduction of nonafluoro- tert -butoxy groups into arenes . The synthetic method gives access to 19 F-labeled probes bearing as many as 72 chemically equivalent 19 F atoms, which allows nanomolar multicomponent analysis of complex mixtures . To achieve a highly sensitive enantioanalysis using NMR, we set out our investigation by the design and synthesis of chiral 19 F-labeled probes bearing massive amounts of 19 F atoms.…”
Section: Resultsmentioning
confidence: 99%
“…The chemosensing nature of the approach allows signal enhancement to be achieved by incorporating more chemically equivalent fluorine atoms. The use of perfluoro- tert -butoxylated probes has enabled the detection of target analytes at nanomolar concentrations, paving new avenues for the application of densely fluorinated compounds in detection . Direct installation of the PFtB group into the aromatic sidewall of the probe is highly preferred because this would bring 19 F atoms closer to the bound analyte to promote more pronounced perturbations on 19 F chemical shifts.…”
Section: Resultsmentioning
confidence: 99%
“…Based on this methodology, palladium pincer complexes bearing 18, 36, and 72 chemically equivalent 19 F atoms are successfully synthesized [79] . Studies showed that the resolving ability of the probe is retained when the number of the incorporated 19 F atoms increases from 18 to 36 (Figure 7A).…”
Section: F‐labeled Probes For Recognition‐enabled Chromatographic 19f...mentioning
confidence: 99%
“…Based on this methodology, palladium pincer complexes bearing 18, 36, and 72 chemically equivalent 19 F atoms are successfully synthesized. [79] Studies showed that the resolving ability of the probe is retained when the number of the incorporated 19 F atoms increases from 18 to 36 (Figure 7A). By using probe 6 bearing 36 equivalent 19 F atoms, the quantitative detection of the analyte at the nanomolar concentration range was achieved (Figure 7B).…”
Section: Palladium-based Probesmentioning
confidence: 99%